Inhibition of O-GlcNAc Transferase Alters the Differentiation and Maturation Process of Human Monocyte Derived Dendritic Cells - Matjaž Weiss; Marko Anderluh; Martina Gobec (Cells, 2021)
The O-GlcNAcylation is a posttranslational modification of proteins regulated by O-GlcNAc transferase (OGT) and O-GlcNAcase. These enzymes regulate the development, proliferation and function of cells, including the immune cells. Herein, we focused on the role of O-GlcNAcylation in human monocyte derived dendritic cells (moDCs). Our study suggests that inhibition of OGT modulates AKT and MEK/ERK pathways in moDCs. Changes were also observed in the expression levels of relevant surface markers, where reduced expression of CD80 and DC-SIGN, and increased expression of CD14, CD86 and HLA-DR occurred. We also noticed decreased IL-10 and increased IL-6 production, along with diminished endocytotic capacity of the cells, indicating that inhibition of O-GlcNAcylation hampers the transition of monocytes into immature DCs. Furthermore, the inhibition of OGT altered the maturation process of immature moDCs, since a CD14medDC-SIGNlowHLA-DRmedCD80lowCD86high profile was noticed when OGT inhibitor, OSMI-1, was present. To evaluate DCs ability to influence T cell differentiation and polarization, we co-cultured these cells. Surprisingly, the observed phenotypic changes of mature moDCs generated in the presence of OSMI-1 led to an increased proliferation of allogeneic T cells, while their polarization was not affected. Taken together, we confirm that shifting the O-GlcNAcylation status due to OGT inhibition alters the differentiation and function of moDCs in in vitro conditions.